Tensions and Dilemmas of Ecotopianism. (1st August 2007) - Pepper, David
Abstract : This paper examines some of many tensions associated with the utopian propensity that underlies much thinking and action in radical environmentalism. They include the tensions inherent within ecotopianism's approach to social change, its desire to embrace ecological universals, its general propensity to face Janus-like in the direction of both modernity and post-modernity, and its tendency towards a polarised stance on scale, and local and global issues. These tensions create dilemmas that are not merely of academic interest: they have practical, tactical and strategic implications, affecting the environmental movement's 'transgressive' potential in the search for ecotopia.